(untitled) - Peterman, Michael A. (Toronto, 1999)
Although Roughing It in the Bush appears on almost every course in Canadian literature, and her writing has been a staple for Canadian literary scholars and historians of succeeding generations, this is the first critical biography of Susanna Moodie. The product of many years of research, it should prove invaluable to anyone interested in Canadian literature and cultural history. Peterman's illustrated biography introduces readers to the complex, driven, and sensitive woman who in 1832 left the cloistered world of middle-class life in England to take up homesteading in the backwoods of Ontario. Drawing upon the letters of Susanna Moodie as well as the full corpus of her work, Peterman looks at her rich and varied life, revealing her tendency to embrace extreme positions, and assessing the various sources of tension in her temperament, especially as they affected her written work. Peterman begins with Moodie's ultimately failed attempt to fashion herself as a spokesperson for Canada's future after she had achieved some celebrity with the publication of Roughing It in the Bush (1852). The chapters that follow provide a larger context for understanding her work, and the effect that notoriety had upon her, as Peterman discusses Moodie's early life in England (1803–32), her experiences in the backwoods of Canada (1832–39), her years in Belleville (1840–69), and her widowhood (1869–85)
Keywords: Authors, canadian ( english ),Moodie, susanna; 19th century,1803-1885